A carta da Terra no meio rural a partir das ações de responsabilidade social das agroindústrias - Nonato, Fernanda Jackeline Aparecida de Paulo (2010)
This study aims to show that the principles of Earth Charter can be embedded in social responsibility practices adopted by agribusinesses companies, located in the Ceara‟s country area. Through Corporate Social Responsibility (CSR), many of the social responsible practices are directly and indirectly linked to values and principles of this declaration. The Earth Charter is the main instrument of this recent initiative to promote the transition to a global society based on a model of shared ethics, which includes respect and care for the community of life, ecological integrity, democracy and a culture of peace. It brings more comprehensive and broader concept of social responsibility to businesses by providing them universal elements structured to recognize their role in humanity. For this, we evaluated the performance of a social responsible agribusinesses company Unit from Group 3 Hearts in Euzébio - Ceará. We used primary source data obtained through a questionnaire and secondary source data drawn mainly from the International Earth Charter. The social responsible practices proposed were analyzed according to the Ethos and the principles and pillars of the Earth Charter. Those were evaluated through the EC-Assess methodology, which enabled them to establish several levels of implementation and levels of recovery of those practices in business. The agribusinesses company has demonstrated a social responsible regarding the implementation and enhancement at various levels of suggested actions. Thus, it was possible to see what is feasible, through responsible management, entering the Earth Charter in the agroindustrial sector and generate gains for all public relations, especially in rural areas, where deprivation reinforce the role of agribusiness as promoters growth and development and maximize its impact in improving the quality of life for this population.